Fiqh of Moderation: An Inclusive, Flexible, and Contextual Approach for Contemporary Muslim Societies - Saiin, Asrizal; Mohd Faizulamri Mohd Saad; Humaira Ahmad (Pusat Kajian Moderasi Beragama dan Ideologi Pancasila UIN Sulthan Thaha Saifuddin Jambi, 2025)
This article examines the concept of fiqh of moderation (wasaṭiyyah) through the framework of inclusive, flexible, and contextual approaches to Islamic jurisprudence. However, the notion of fiqh of moderation is not a new term, and previous studies have yet to elucidate the mechanism through which inclusive, flexible, and contextual approaches can effectively serve as models of religious moderation. This article aims to address this lacuna by exploring their practical application to contemporary challenges in Muslim societies. This article uses a qualitative approach with a literature study type of research (library research). This article concludes that the inclusive approach of fiqh of moderation encompasses the diversity of legal opinions (madhāhib) and fosters interfaith dialogue. The flexible approach employs ijtihād to address emergent issues while upholding shariah principles. The contextual approach takes into account socio-cultural specificities in legal interpretation, guided by maqāṣid al-sharīʻah (the higher objective of Islamic law). These findings indicate that the integration of these approaches within the fiqh of moderation framework results in the creation of a balanced methodology. This methodology preserves the core principles of shariah while enabling adaptability to modern circumstances. This article contributes to the discourse on religious moderation by proposing a theoretical framework that seeks to harmonize Islamic tradition with contemporary social dynamics. The framework functions as a resource for scholars, policymakers, and Muslim communities seeking to implement moderate religious perspectives that promote social harmony while maintaining religious authenticity.